Dubašnica Social Club of America Inc. (New York) - Galović, Tomislav (2013)
Otok Krk je poznat po brojnom iseljeništvu koje je svoj novi dom i zaposlenje pronašlo u Sjedinjenim Američkim Državama, napose u New Yorku i okolici. Proces iseljavanja s otoka započeo je još u 19. stoljeću iz ekonomskih i političkih razloga. Okvirno se procjenjuje da je do 50-ih godina prošlog stoljeća oko 640 krčkih obitelji emigriralo u SAD, ali taj je trend nastavljen i kasnije pa sporadično čak i u naše vrijeme. Među krčkim iseljenicima po broju prednjače Omišljani i Dubašljani1 pa je bilo razumljivo da su se oni s vremenom u novoj domovini počeli organizirati u zavičajna društva. Prvo su svi Krčani zajedno 1899. osnovali potporno društvo koje se od 1934. naziva Croatian Benevolent Society of st. Nicholas of Island Krk in New York, inc. (Hrvatsko dobrotvorno društvo sv. Nikole od otoka Krka u New Yorku udruženo). No započinju i osnivanja lokalnih društava pa tako 1940. Dubašljani u New Yorku utemeljuju svoje društvo pod imenom Dubašnica Social Club of America Inc. (Društveni klub Dubašnica u Americi).
The island of Krk is known for its numerous emigrants that have found their new homes and employments in the USA, especially in New York and its surroundings. The process of emigration set in back in the 19th century for economic and political reasons. Among the emigrants from the Krk island those from Omišalj and Dubašnica are the strongest in number. It was therefore understandable that with time they would start organizing themselves in the new homeland into ethnic associations. However, there were also some local societies so that in 1940 the emigrants from Dubašnica founded an organisation called the Dubašnica Social Club of America Inc. The club’s rules, to be found here in an appendix, were approved on May 20th, 1940. They state that the mission of the club is „to establish and maintain closeness among those born in Dubašnica, members of their families and descendants, to strengthen friendship among the members” as well as to help the members gain US citizenship. Thomas Samara was elected the first president. The club maintained various activities: social meetings, parties, common dinners, picnics, Holy Masses for the deceased, relief actions for the old country. The club still exists today and is accordingly active among our emigrants, which have been living in New York for many generations now, gathering and reminding them of their origin and the old country of their parents and relatives.
Projekt MZOS
HRV-ENG